PENENTUAN TINGKAT KEMATANGAN TERMAL MINYAK MENTAH ( CRUDE OIL ) DARI LADANG MINYAK LIRIK Kab. INDRAGIRI HULU, RIAU - Cindya Afrina; Emrizal Mahidin Tamboesai; Halida Sophia (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Lirik  oil field  is one of the oil-producing layers  that  is  located in  Indragiri  Hulu  Riau  province, situated at ± 140 km South of the city of Pekanbaru with the area of ± 12 km2.  There is no researchon  Lirik oil fields, at  on the  maturity level of petroleum using  the methylphenantrene  index parameters on oil wells, therefore  this study aimed   to determine  the level of thermal maturity of  Lirik  oil.  Determination of thermal maturity was done by taking  two samples from two different wells of Lirik oil field, Riau. In this study the thermal maturity determination was  done using two parameters,  the  parameters of isoprenoid and n-alkanes in saturated  fractions and  characterized using gas chromatography (GC-FID), this parameter was  the  initial  parameter  in the determination of thermal maturity. Determination of the level of thermal maturity of petroleum  enhanced with  Metilphenantrene  index parameter on aromat fractions were characterized using gas chromatography -mass spectroscopy (GC-MS). Determination of thermal maturity level using the parameter index was determined by looking at the value Metilphenantren MPI-3 and MPR (Methylphenantrene ratio). The results of the determination of thermal maturity at saturated  fraction using the ratio of n-alkanes and isoprenoid indicated  that oil from  Lirik  oil wells, Riau was  already ripen. This was confirmed by the parameters that have Metilphenantrene  index values  ranged MPI-3 0709; MPR 0755 and 0699 ranges; 0.756. The values  of these parameters Metilphenantren index showed that  crude oil from two wells Lirik, Riau has a low maturity level.